Advances in financial planning and forecasting - Lee, Cheng F. (Amsterdam; JAI, 2000)
Part of a series which focuses on advances in futures and options research, this volume discusses a variety of topics in the field.
&#x000A
lje 10/9/13
Loans
Keywords: Finance -- Econometric models; Corporations -- Finance -- Econometric models; Stock price forecasting -- Econometric models